31 Endothelial microparticles and endothelial function in active systemic lupus erythematosus (SLE): biomarkers of vascular injury?. Issue 20 (23rd September 2011) - Parker, B; Zaki, A; Haque, S; Bruce, I N; Alexander, M Y
Abstract : SLE is associated with endothelial dysfunction. Endothelial microparticles (EMPs) are subcellular particles considered to reflect endothelial damage. We aimed to quantify endothelial function and EMPs in a cohort of SLE patients with active disease, and investigate changes in response to treatment in a smaller subset of patients. Methods: 12 patients (mean age 41.2 (SD 14.9) years) with active SLE were assessed for disease activity, repeated at 4 months in 5 patients. Four age-matched healthy controls (mean age 40.5 (SD 14.5) years) were assessed once. Endothelial function was assessed using peripheral arterial tonometry (EndoPAT 2000©). EMPs were quantified (number/ml) using flow cytometry after staining platelet-poor-plasma with the cell surface markers CD31, CD42 and Annexin-V. Events positive for annexin-V and CD31, and negative for CD42, were classified as EMPs. Results: At baseline, mean EMP count was 21 782/ml (SD 11 946) in SLE cases, and 13 441/ml (SD 2347) in controls (p=0.04). There was a trend towards reduced endothelial function in SLE (mean Reactive Hyperaemic Index (RHI) 2.04 (SD 0.7) vs 2.62 (SD 0.5); p=0.18). In those with follow-up data, the mean EMP count decreased from 32 709/ml (SD 7186) to 15 662/ml (SD 5658; p=0.04) and RHI improved (mean RHI 1.75 (SD 0.2) vs 2.72 (SD 1.2; p=0.16) with better disease control. Conclusions: Active SLE is associated with higher levels of EMPs compared to controls, reflecting endothelial damage. Reducing disease activity reduces EMP numbers and may improve endothelial function. EMPs may therefore serve as markers of both disease activity and vascular injury.